Amalgamation of Multiple Temporal and Spacial Frames in “Sunlight” by Seamus Heaney - Idris, Memoona (Journal of Research in Humanities, 2023)
Time and space are the two dimensions of any work of art. How a writer employs these two decides how good a piece may be. Many writers use it two add depth to there work and so does Heaney, in many of his poems. “Digging” and other such poems are an example of these, what sets “Sunlight” apart from other such poems however is the ease and mastery with which Heaney amalgamates various temporal and special shifts in it. This paper seeks to analyze which frames of time and space are created in the poems and how Heaney blends them to merge into each other.